(untitled) - United States; Department of State (Washington, 1946)
Contents Development of policy trough Allied Cooperation Surrender Planning for Future Policy of Japan Occupation Politics War Criminals Reparations Education Economics War Industry and the Zaibatsu Labor International Trade The Future Appendixes.
Keywords: Tái thiết (1939-1951),Reconstruction (1939-1951); Nhật Bản,Japan